Pelatihan Penulisan Karya Tulis Ilmiah Bagi Peserta Didik MAN 3 Jombang - Mucharommah Sartika Ami; Wisnu Siwi Satiti; Fatikhatun Nikmatus Sholihah (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2021)
Scientific writing is a language skill that requires active thinking ability, and is included in the literacy competence that must be mastered by students. Scientific writing skills can be achieved through concrete and integrated learning activities that involve students actively. This community service activity aims to train students in MAN 3 Jombang to be able to produce scientific writings that are in accordance with applicable writing rules. The stages carried out in this community service activity were socialization, training, and assistance. Monitoring and evaluation are also carried out at each stage. This activity was carried out at MAN 3 Jombang from August 2020 to October 2020. The participants of this activity were 20 people who were class students X, XI, and XII. As many as 90% of participants participated in the activity enthusiastically and were able to produce scientific writing which were included in several national youth scientific writing competitions. The other 10% of participants had not been able to produce scientific papers in accordance with the rules of writing, so that they could not be included in the competition. The follow-up plan for this community service activity is to optimize the extracurricular Youth Scientific Group at the school, so that more students are able to produce good scientific papers.